INCONSISTENCIES IN THE APPLICATION OF ARTICLE 71 PARAGRAPH (3) OF THE JUVENILE JUSTICE SYSTEM ACT IN CRIMINAL VERDICTS AGAINST CHILDREN: A NORMATIVE REVIEW OF THE KALABAHI, ATAMBUA, AND AMBON DECISIONS - Anindita, Raras Natasya; Aprilianda, Nurini; Istiqomah, Milda (NOMOI Law Review, 2025)
This study examines the implementation of Article 71 paragraph (3) of Law No. 11 of 2012 concerning the Juvenile Justice System (UU SPPA), which regulates the replacement of criminal fines with work training in cases involving juvenile offenders. This provision aims to ensure fairer protection for children through a corrective, recovery oriented approach. The research employs a normative legal method, combining statutory and case based approaches, and analyzes three first instance court decisions from Kalabahi, Atambua, and Ambon. The findings reveal inconsistencies in the application of the provision, as not all verdicts fully adhere to the mandated substitution of fines with work training as stipulated in the UU SPPA. These disparities highlight the need for greater uniformity and comprehension of the applicable norms to guarantee optimal protection of children's rights. Work training should not be viewed merely as an alternative sanction but as a rehabilitative measure aligned with the principles of restorative justice. This study recommends the development of technical guidelines and the strengthening of institutional capacity to support sanctions that uphold child protection and sustainable justice values.